CIDE Family-Mediated Unique Lipid Droplet Morphology in White Adipose Tissue and Brown Adipose Tissue Determines the Adipocyte Energy Metabolism - Nishimoto, Yuki (J Atheroscler Thromb, 2017)
White adipose tissue (WAT) stores energy as triacylglycerol in preparation for fasting state. In contrast, brown adipose tissue (BAT) consumes energy and produces heat in a cold environment. One of the major differences between these two adipose tissues is the morphology of the intracellular lipid droplet (LD), which is large and unilocular in WAT and small and multilocular in BAT. Although the fat-specific protein 27 alpha (FSP27α), belonging to the cell death-inducing DNA fragmentation factor A (DFFA)-like effector (Cide) family, was known to be indispensable for large unilocular LD formation in WAT, the mechanism that regulated small multilocular LD formation in BAT remained unknown. We recently uncovered that FSP27β, a novel isoform of FSP27 abundantly expressed in BAT, plays a crucial role in small multilocular LD formation by inhibiting the homodimerization of CideA in BAT. We speculate that unilocular LD formation is ideal for efficient lipid storage in WAT because lipolysis from the LD surface is restricted due to the minimum LD surface area. In addition, hydrolyzed free fatty acid (FFA) and glycerol can efficiently flow out into the circulation from the cell surface. In contrast, small multilocular LD formation is ideal for efficient intracellular lipolysis from the LD surface and the subsequent facilitation of FFA transport to mitochondria that are adjacent to LDs for β-oxidation in BAT. Thus, intracellular LD morphology is closely related to the functions and characteristics of adipose tissues. Given that the browning of adipose tissue leads to enhanced energy expenditure and the prevention of obesity, clarification of the mechanism with respect to intracellular LD formation is very meaningful.